Analisis Pengaruh Covid-19 dan Makroekonomi Terhadap Jakarta Islamic Index (JII) - Nurul Siti Jahidah (Universitas Kuningan, 2022)
The Covid-19 pandemic has caused instability in the capital market, including the Islamic capital market, such as the Jakarta Islamic Index (JII). Besides Covid-19, macroeconomic factors can also influence the level of investment in the Islamic capital market. The data used is monthly time series data from March 2017 to March 2022, using the Vector Error Correction Model (VECM) method. This method aims to analyze the relationship between Covid-19 and macroeconomic factors to the Jakarta Islamic Index (JII) in the short and long term. Based on the research, in the short and long term period, Covid-19 variable significantly affect the JII index. On the other hand, the variables that significantly affected JII in the long term are the money supply which is, positively significant, and inflation negative significant.